Features of digital ethnography as a variety of ethnography in sociology - Zheshka, Yahor I. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The attitudes and principles of digital ethnography as a kind of ethnography in sociology are considered. Its methodology is used to study the social and cultural aspects of virtual communities. The article describes the main features of digital ethnography by comparing this methodology with ethnography in sociology. At the same time, the article reflects the fact that digital ethnography preserves the continuity of a number of attitudes and principles of ethnography in sociology, adapting them to a new specific object of research.
Keywords: virtual communities; methodology; ethnography; digital ethnography; communication; qualitative research